Estimation of Some Metals in Children’s Colorful Modeling Clay Sold in the Markets of Erbil City, Kurdistan Region, Iraq - Aveen Faidhalla Jalal; Hawraz Sami Khalid; Iman Tayib Yasin; Mhabat Rashid Xanamir (Zanco Journal of Pure and Applied Sciences, 2020)
Toxic heavy metals are commonly introduced in the manufacturing of various children's products. In this study, nine different types of modeling clay brands collected from several markets in Erbil city were analyzed to assess the content of heavy metals including Cd, Cr, Cu, and Ni. The metals analyses were performed on different colors available in each of the purchased brands. Strong acids such as nitric acid (HNO3 65%), and perchloric acid (HClO4 70%) were performed to digest samples. Concentrations of the selected metals were determined using a flame atomic absorption spectrophotometer (FAAS). Data showed that numbers of examined clays samples detected with Cr, Cd Cu, and Ni metals were 0, 5, 36, and 40 out of 54 examined clay samples, respectively. Ni and Cu were found in varying concentrations in most (detected in 8 brands out of 9 collected clay brands) of the examined clay brand samples. The total of the detected metals load in the nine analysed brands were as follows; Chinese-3 (221.41 mg/kg) > Italian (75.84 mg/kg) > Chinese-4 (68.00 mg/kg) > German (61.31 mg/kg) > Chinese-6 (58.67 mg/kg) > Turkish (54.05 mg/kg) > Chinese-5 (52.51 mg/kg) > Chinese-1 (23.7 mg/kg) > Chinese-2 (23.31 mg/kg). Data confirms that the concentrations of the selected metals in whole examined samples were below European Union permissible limits (EN 71-3:2013, Category-I) for the migratable metals in pliable clay toys except one clay sample (819.2 mg/kg of Cu in blue clay color). An analysis of variance (ANOVA) was applied to find the presence of significant differences among analysed brands of modeling clay samples.